The toy-shop / by Robert Dodsley. - Dodsley, Robert, 1703-1764. (Tufts University. Tisch Library., 2015)
1 online resource (pages [40]-56); Caption title.; Published in A Collection of the most esteemed farces and entertainments performed on the British stage, v. 3.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.